THE INFLUENCE OF LEADERSHIP STYLE AND PRINCIPAL'S SUPERVISION COMPETENCE ON THE PERFORMANCE OF TEACHERS - Handayati , Nadia Arsita (Managere: Indonesian Journal of Educational Management, 2023)
The focus of this study is to investigate the relationship between the leadership style and supervision competence of school principals with teacher performance in SD Negeri Tanjung Putus. The main objective is to explore the extent to which transformational leadership styles and principals' supervision competencies affect teacher performance, as well as to provide a deeper understanding of the factors that can improve the quality of education at the primary school level. Based on these cases, this study used causal associative research with a quantitative approach. This study was combined from respondents using questionnaires or questionnaires. The population and illustrations in this study came from 10 Tanjung Putus State Elementary School teachers or respondents. The method of collecting illustrations uses bored sampling. In this study using Multiple Linear Regression Analysis. The results showed a significant relationship between transformational leadership style and principal supervision competence with teacher performance at SD Negeri Tanjung Putus. Analysis of the data showed that a motivating leadership style and a clear vision of the principal had a significant positive impact on teacher performance. In addition, strong supervision competencies, including the ability to provide constructive feedback and effective support to teachers, have also been shown to contribute positively to teacher performance in the school. The implications of this study highlight the need to improve the quality of leadership and supervision of school principals to improve teacher performance at SD Negeri Tanjung Putus, which is expected to have a positive impact on the quality of education in the school and can be a model for other schools in efforts to improve the overall quality of education.